Limosilactobacillus reuteri DSM 17938 and ATCC PTA 6475 for the treatment of moderate to severe irritable bowel syndrome in adults: a randomized controlled trial - Cruchet, Silvia; Hirsch, Sandra; Villa-López, Diana; Moreno-Portillo, Mucio; Palomo, Juan C.; Abreu-Abreu, Ana T.; Abdo-Francis, Juan M.; Jiménez-Gutiérrez, Carlos; Rojano, Martin; López-Velázquez, Gabriel; Gutiérrez-Castrellón, Pedro (Frontiers in Gastroenterology, 2024)
Background. Irritable bowel syndrome (IBS) is a common functional gastrointestinal disorder in adults. Systematic reviews with meta-analyses have demonstrated the efficacy and safety of probiotics in improving symptoms. Aim. To demonstrate the efficacy and safety of Limosilactobacillus reuteri (L. reuteri) DSM 17938 combined with L. reuteri ATCC PTA 6475 regarding improving the symptoms associated with IBS in adults. Methods. A randomized, double blind, placebo controlled clinical trial conducted in 140 adults aged 18 to 65 years with diagnosis of IBS (Rome IV). After 2 weeks of washout, subjects were randomized to receive 2x108 colony forming units (CFUs) of L. reuteri DSM 17938 combined with L. reuteri ATCC PTA 6475 + standard of care or placebo + standard of care for 14 weeks, followed by a post-intervention period of 2 additional weeks. Changes in gastrointestinal symptoms (GSRS-IBS), stool pattern (Bristol scale), quality of life, depression and anxiety, frequency of adverse events, and faecal calprotectin were evaluated. Results. 70 subjects were allocated to L. reuteri and 70 to Placebo. During the pre-randomization phase, no differences were observed between the groups in terms of IBS associated symptoms and stool consistency. Starting at 6w of intervention, subjects in group L. reuteri showed a significant improvement on IBS associated symptoms, (p < 0.01). Significant improvement was also observed in faecal calprotectin concentration in group L. reuteri at the end of interventions (30.2 ± 11.8 mg/g of stool in Group L. reuteri and 41.6 ± 10.7 mg/g in Group Placebo, p = 0.019). The frequency of adverse events was similar between groups. Conclusions. A twice-a-day intervention for 14 weeks is safe and effective, reduces the symptoms associated with IBS in adults aged 18 to 65 years, improves stool consistency, and reduces symptoms associated with anxiety after 6 weeks.